Statystyczna analiza dywidendy w wybranych spółkach na Giełdzie Papierów Wartościowych w Warszawie - Łuniewska, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
A dividend is one of main important information in investment decision. It has particular meaning on the well developed capital markets. A statistical analysis of dividend in chosen non-financial companies quoted on the Warsaw Stock Exchange is carry out in the paper. These companies were set in index WIG20 in March 2005. A dividend is still in Poland treated as additional information in investment decisions. It must be said, that more and more companies pay attention to increasing role and meaning dividend on the capital market.So that, the analyses in the paper referred dividend and some chosen ratios connected with it. During researches were estimated some distribution parameters to characterize in synthetic point of view this problem. All analyses were done in period 1997-2003. The main aim in those analyses was to show meaning of dividend issue on the Polish capital market. Beside it, such researches could help to indicate the level of development Polish capital market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 381-390